Food habits of Oligoryzomys longicaudatus (Rodentia) in a steppe–forest transitional area of Argentinean Patagonia - Polop, Francisco (2014)
We described the spatial and seasonal variation of feeding habits of Oligoryzomys longicaudatus in four environments of the steppe-forest transition zone of Argentinean Patagonia. Composition of fecal pellets collected from live-trap captures was determined with microhistological techniques using an identification key of representative plants of our study areas. Fruits and seeds constituted 57.2% of O. longicaudatus diets, followed by foliage (26.8%) and arthropods (16.0%). Fruits and seeds, foliage parts, and arthropods were primarily found in individuals from shrublands, forests, and peridomestic areas, whereas foliage predominated in pastures. Similarity index revealed differences between pastures and the other environments. Diet in shrubland showed differences among seasons, but not among years. Fruits of Rosa spp. constituted the main food consumed in shrubland, forest and peridomestic environments mainly in autumn and winter, whereas in spring and summer high proportions of arthropods and other items were eaten. Thus, O. longicaudatus could be described as frugivorous in this region, explained by an opportunistic behavior and the spatial variation of available resources.